Principles of social change - Jason, Leonard (New York : Oxford University Press, 2013)
This text is written for those who are impassioned and driven by social justice issues in their communities and seek practical solutions to successfully address them. Leonard A. Jason, a leading community psychologist, demonstrates how social change can be accomplished and fostered by observing five key principles.
Description based on online resource; title from home page (viewed on Jan. 7, 2013).
Includes bibliographical references and index.
Keywords: Social change; Social action; Community development